Keanekaragaman dan Sebaran Tumbuhan Kepuh (Sterculia foetida) di Kabupaten Lamongan - Nurul Imamah; Sitti Nur Ilmiah; Slamet Ifandi (Jurnal Matematika dan Sains (JMS), 2022)
Kepuh is a species of plant from the Malvaceae family that has a large body. The distribution of Kepuh is found in Southeast Asia, especially in the tropics and subtropics. Kepuh is one of the endangered species, because it is rarely found in primary and secondary forests. In terms of utilization, it is still very limited, only planted as yard plant and garden fences. This study aims to determine the diversity of Kepuh in Lamongan district. This type of research is descriptive analytic with a quantitative approach. Data collection techniques used are survey and observation. The results of this study are the diversity of Kepuh includes (1) the diversity of families that dominates the Fabaceae family, (2) the diversity of habitus of Kepuh that dominates is seedlings, (3) the diversity of habitats that dominates is plantations land, (4) the highest INP value of Kepuh is 28,29% in the medium category.